Halal Tourism Management Challenges In Realizing Religious Moderation In Indonesia - Hadi Peristiwo (Universitas Mathla’ul Anwar Banten, 2023)
Halal tourism in Indonesia is becoming a hot topic of conversation because it raises pros and cons among the public. Many argue that the existence of halal tourism will kill local wisdom and turn an area into a religious area. Religious moderation is interpreted as a balanced religious attitude between the practice of one's own religion and respect for the religious practices of other people of different beliefs. This research uses a qualitative approach. The method used in this research is descriptive analysis. From the results of the study can be obtained conclusions that religious moderation is a middle way in an effort to bring harmony to differences in perceptions that occur in understanding religion. Management halal tourism has great potential in planning the creation of religious moderation in Indonesia, so the challenge contained in halal tourism is not become a barrier of the main actors to be able to sow the seeds of moderation in preventing the spread of the ideology of violence. Keywords : Halal Tourism, Religious Moderation, Indonesia